Pengaruh Kualitas Produk Dan Digital Marketing Terhadap Keputusan Pembelian Kopi Janji Jiwa Di Jakarta Pusat - Dewi, Latifah; Lahat, Mohammad Amas; Utama, Dani Chandra (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Competition in the coffee business is getting tougher with the emergence of various coffee brands, one of which is Janji Jiwa coffee. Janji Jiwa experiences inconsistent taste from its products, in addition to its digital marketing strategy being considered less authentic because it uses influencer content. The purpose of this study is to analyze the influence of product quality and digital marketing on purchasing decisions for Janji Jiwa coffee in Central Jakarta. The method in this study uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to 100 respondents of Janji Jiwa coffee consumers in the Central Jakarta area, then the data were tested using SPSS 23. Data analysis was carried out using multiple linear regression to determine the influence of product quality and digital marketing variables on purchasing decisions. The results of this study indicate that Product Quality has a positive and significant influence on purchasing decisions with a calculated t value of 8.685> t table 1.984 and a sign value of 0.000 <0.05, Digital Marketing has a positive and significant influence on purchasing decisions with a calculated t value of 2.127> t table 1.984 and a sign value of 0.036 <0.05, and simultaneously Product Quality and Digital Marketing have a positive and significant influence on Purchasing Decisions with a calculated f value of 107.694> f table 3.09 and a sign value of 0.000 <0.05.